2021
DOI: 10.21608/ejhc.2021.138119
|View full text |Cite
|
Sign up to set email alerts
|

Otago Exercise Program (OEP): A Golden Technique on Health Status and Risk of Falls among Older Adults with Chronic Diseases

Abstract: Background: Fall is a worldwide health problem, leading cause of disability, resulted from declining physical function among elderly people. Otago exercise is a strength and balance program designed to prevent falls and enhance health status among the elderly. Aim: to appraise the effect Otago Exercise Program (OEP) on health status and risk of fall among older adults with chronic disease. Design: A quasi-experimental research design was utilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Those findings were in the same line with Abd-Elraziek et al (13) in Egypt who clarified that the most prevalent chronic diseases among their studied sample were hypertension, Diabetes and arthritis (60.4%, 47.9% & 27.8%). Also, Darjani et al (17) in Iran agreed with the present study as they found that the most common comorbidities of elderly subjects were hypertension (87%) and diabetes mellitus (18%).…”
Section: In Terms Of Medical Historysupporting
confidence: 91%
See 2 more Smart Citations
“…Those findings were in the same line with Abd-Elraziek et al (13) in Egypt who clarified that the most prevalent chronic diseases among their studied sample were hypertension, Diabetes and arthritis (60.4%, 47.9% & 27.8%). Also, Darjani et al (17) in Iran agreed with the present study as they found that the most common comorbidities of elderly subjects were hypertension (87%) and diabetes mellitus (18%).…”
Section: In Terms Of Medical Historysupporting
confidence: 91%
“…Similar to that finding, El Sayed & Ewees (12) found in their Egyptian study that most of their studied subjects were married. This finding disagreed with Abd-Elraziek et al (13) who stated that about half of their subjects were married and the others were among divorced or widow status.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In any healthcare facility, including those that provide care at home, nurses have a significant responsibility to improve health and decrease falls among elderly patients with chronic diseases. By being instructed, ready, and motivated to do so, seniors can use the Otago Exercise Program (8).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it was determined that the OEP group gave better results than individual exercises in terms of commitment and compliance (Albornos‐Muñoz et al, 2018; Jahanpeyma et al, 2021; Shubert et al, 2017; Zou et al, 2022). It is emphasized that nurses can deliver the OEP, especially those who work in primary care, and so it is the important for the roll‐out of the OEP that it is tested in different countries and offered routinely in differing health facilities (Albornos‐Muñoz et al, 2018; Mohamed Ebrahim Abd‐Elraziek et al, 2021).…”
Section: Introductionmentioning
confidence: 99%